IL-4 plays an essential role in DnaJ-ΔA146Ply-mediated immunoprotection against Streptococcus pneumoniae in mice. (March 2022) - Hu, Yi; Li, Lian; Xu, Wenchun; Wu, Kaifeng; Xiao, Jiangming; Peng, Yang; Liu, Yusi; Yin, Yibing; Zhang, Xuemei
Highlights: IL-4 does not affect DnaJ-ΔA146Ply-mediated antibody production or effect. IL-4 deficiency changes cellular immune response induced by DnaJ-ΔA146Ply. IL-4 enhances opsonic phagocytosis of neutrophils partially by activating Syk. Abstract: The fusion protein DnaJ-ΔA146Ply is protective against pneumococcal infections in mice. However, we found that immunized IL-4 −/− mice showed significant lower survival rates and higher bacterial loads than did wild-type (WT) mice after being challenged. We explored the role of IL-4 in the protective immunity conferred by DnaJ-ΔA146Ply. Our results showed that there were no significant differences in antibody titers between immunized WT mice and IL-4 −/− mice. The bacterial loads of passively immunized IL-4 −/− mice were significantly higher than those of WT mice, while mice immunized with anti-DnaJ-ΔA146Ply serum from WT and IL-4 −/− mice showed similar capacity for bacterial clearance. DnaJ-ΔA146Ply-dependent phagocytosis of IL-4 −/− neutrophils was significant decreased compared with that of WT neutrophils. The levels of Syk and phosphor-Syk in IL-4 −/− neutrophils were decreased compared with those in WT neutrophils. Additionally, Splenocytes in IL-4 −/− mice triggered significantly higher levels of IFN-γ and IL-17A than did splenocytes in WT mice. Taken together, our findings illustrate that IL-4 deficiency does not influence the antibody production or antibody effect, but change the cellular immune response induced by DnaJ-ΔA146Ply. Additionally, IL-4 can enhance the antibody-dependent phagocytosis of neutrophils partially by activating Syk and participate in the protective immunity induced by DnaJ-ΔA146Ply.